1991
DOI: 10.1093/infdis/164.5.864
|View full text |Cite
|
Sign up to set email alerts
|

Decreased Serum Dehydroepiandrosterone Is Associated with an Increased Progression of Human Immunodeficiency Virus Infection in Men with CD4 Cell Counts of 200-499

Abstract: Dehydroepiandrosterone (DHEA) and its interconvertible sulfate derivative (DHEA-S) are human androgenic steroids that have been reported to inhibit viral expression and have been associated with a decreased risk of cancer. The relationship between serum DHEA and DHEA-S levels and subsequent progression to AIDS was investigated in a sample of human immunodeficiency virus (HIV)-infected men from the San Francisco Men's Health Study followed prospectively since 1984. Among 108 men seropositive for HIV at study en… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
29
0
1

Year Published

1992
1992
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 76 publications
(34 citation statements)
references
References 19 publications
4
29
0
1
Order By: Relevance
“…Recent studies have shown that low DRIEA levels can independently predict disease progression of HIV infection to AIDS, and it was suggested that DHEA may have a therapeutic value in HIV patients (13). On the basis of our data we suggest a possible mechanism for DHEA involvement in HIV patients and a rationale for treatment: expression of HIV can be activated by TNF (7,25).…”
Section: Discussionsupporting
confidence: 58%
“…Recent studies have shown that low DRIEA levels can independently predict disease progression of HIV infection to AIDS, and it was suggested that DHEA may have a therapeutic value in HIV patients (13). On the basis of our data we suggest a possible mechanism for DHEA involvement in HIV patients and a rationale for treatment: expression of HIV can be activated by TNF (7,25).…”
Section: Discussionsupporting
confidence: 58%
“…In contrast to Christeff's ÂŽ ndings, Jacobson et al 15 reported a trend association between decreased DHEA prior to the development of KS or lymphoma. Another study by Rosenthal and colleagues 16 failed to ÂŽ nd elevated DHEA or other androgens in 10 men with KS.…”
Section: Does Testosterone Exacerbate Kaposi's Sarcoma?mentioning
confidence: 62%
“…Among HIV-infected men, DHEA is used to increase energy and stamina, increase muscle mass, and even to improve the outcome of HIV infection [35]. Indeed, endogenous levels of DHEA appear to correlate with prognosis in a number of illnesses, including HIV infection [3,25], and intake of DHEA reduces manifestations of depression and improves the sense of well-being [16,28,36].…”
Section: Discussionmentioning
confidence: 99%
“…Serum concentrations of DHEAS decline with age [2] and are low in numerous disease states, including HIV infection [3] and depression [4].…”
Section: Introductionmentioning
confidence: 99%